STRATEGI USTADZ DALAM MENGAJARKAN MATERI SHALAT DI PENGAJIAN MAJELIS DARUL ILMI DI DESA KUBANGAN TOMPEK, KECAMATAN BATAHAN, KABUPATEN MANDAILING NATAL - Monika; Sokon Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Prayer is the pillar of Islam that carries not only ritual dimensions but also spiritual, moral, and social values. In rural communities, strengthening the understanding and practice of congregational prayer faces several challenges, particularly in terms of limitedknowledge and consistency in implementation. This study aims to explore the strategies employed by Islamic teachers (ustadz) in teaching the practice of congregational prayer at the Darul Ilmi Study Assembly in Kubangan Tompek Village, Batahan Subdistrict, Mandailing Natal Regency. This research applied a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving both the ustadz and community members, then analyzed using Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the ustadz utilized interactivelectures, reinforcement through Qur’anic verses and hadiths, and communicative language tailored to the daily lives of the participants. These strategies proved effective in improving the participants’ understanding of prayer procedures while also instillingspiritual and social values. The challenges identified include the ustadz’s inconsistent attendance and external factors such as weather conditions that hinder the continuity of the study sessions. In conclusion, the effectiveness of prayer education in the assembly is strongly influenced by the ustadz’s consistency and the application of strategies aligned with the rural community context.